Knowledge and Intention to Use Personal Protective Equipment among Health Care Workers to Prevent Tuberculosis - Hasanah, Hasanah; Pudji Setiawati, Elsa; Apriani, Lika (Althea Medical Journal, 2016)
Background: Tuberculosis (TB) is one of the main world health problems. Indonesia has the fourth highest incidence in the world. Tuberculosis is very infectious, but it can be prevented in high risk group such as health care worker by using personal protective equipment (PPE). This study aimed to reveal knowledge and intention to use PPE among health care worker to prevent TB transmission in Public Health Center (Pusat Kesehatan Masyarakat, Puskesmas) in Bandung.Methods: Descriptive study was conducted from September to October 2014 in 15 Puskesmas in Bandung. Those 15 Puskesmas had been reported as having the highest incidence in TB cases. Ninety seven health care workers were assessed using questionnaire. Samples were obtained using purposive sampling method. Data were collected and analyzed for frequency and proportion.Results: Among 97 health care workers, 76 (78.4%) had good knowledge, 16 (16.5%) had sufficient knowledge, and 5 (5.2%) had poor knowledge. Based on intention of PPE usage among health care workers, it was found that 41.2% had positive intention and 58.8% had negative intention.Conclusions: Most of health care workers have good knowledge about TB transmission, however, intentions to use PPE are low. [AMJ.2016;3(1):120â5]DOI:Â 10.15850/amj.v3n1.713